ASSOCIATION BETWEEN MUSCLE STRENGTH, GAIT SPEED AND QUALITY OF LIFE IN OLDER ADULTSA WITH SARCOPENIA:A CROSS-SECTIONAL STUDY - Manchev, Lejla; Trajanovikj, Savo (Journal of Morphological Sciences; Vol 8 No 2 (2025): JMS, 2025)
Introduction: Sarcopenia is a progressive and generalized skeletal disorder that is associated with increased likelihood of adverse outcomes, including falls, fractures, physical disability, and mortality. Muscle strength is now considered more important than muscle mass in diagnosing sarcopenia. Material and methods: This is a cross-sectional study with 75 patients in total. The patients included are from nursing homes in the Republic of North Macedonia and outpatients, aged 60 and over. The patients included were diagnosed with sarcopenia through assessment of muscle mass (bioimpedance analysis), physical performance (gait speed), muscle strength (handgrip strength), and a SARC-F score equal to or over 4. Patients diagnosed with sarcopenia fulfill the - 36 questionnaire for assessment of quality of life. Results: In terms of Muscle Strength (MS), the patient group without sarcopenia (Z = 3.27) and p = 0.001 has statistically significantly higher Muscle Strength (handgrip strength) compared to the patient group with sarcopenia. Participants with sarcopenia have a significantly lower gait speed compared to those without sarcopenia (Z = -5.83, p < 0.001). Conclusion: If Muscle Strength is increased by only 1kg, the quality of life in patients with sarcopenia increases on average. The test result shows a significant difference — people with sarcopenia walk more slowly. Routine handgrip and gait speed assessments in older adults can identify at-risk individuals before major functional decline occurs. Improvements in either measure indicate effective intervention and reduced sarcopenia-related risk. Key words: sarcopenia, muscle strength, gait speed, quality of life.